The Effect of Exposure to Noise and Vibration and Ergonomic Factors on Sleep Quality and Musculoskeletal Disorders in Bus Drivers in Iran - Somayeh Rahimimoghadam; Narges Khanjani; Mahdi Jalali; Fatemeh Khorashadizadeh; Ayda Shahmohammadi (International Journal of Environmental Health Engineering)
Aim: City bus drivers are exposed to various harmful factors such as noise and vibration, which may cause adverse health effects. This study was conducted with the aim of investigating the impact of exposure to noise, vibration, and ergonomic factors on the quality of sleep and the prevalence of musculoskeletal disorders (MSDs) among city bus drivers in Neyshabur, Iran. Methods: Sixty-two city bus drivers from Neyshabur, Iran, participated in this study. Their level of exposure to noise was measured according to the ISO 5128:1980 standard, and the level of exposure to vibration was measured according to the ISO 2631 standard. Sleep quality (SQual) was evaluated with the Pittsburgh SQual Index, and the prevalence of MSDs was surveyed with the Nordic questionnaire. Data were analyzed with R version 4.3.2. Results: The average ± standard deviation (SD) exposure to noise was 83.25 ± 4.12 dB, and the average ± SD exposure to vibration was 0.14 ± 0.04 m/s2. The SQual of 46.77% of drivers was bad, and 69.35% of drivers suffered from MSDs in at least one of their body parts. The results of this study showed as drivers’ age increased, the chance of having good SQual decreased (odds ratio [OR]: 0.9, 95% confidence interval [CI]: 0.81–0.99). Sleep disorders were more common among drivers whose buses had spring seats (OR =3.17, 95% CI: 1.07–9.40). Conclusion: Almost half of the drivers had unfavorable SQual and suffered from MSDs. The type and quality of the seats, the age of the bus driver, and the bus type were among the most important factors affecting the quality of sleep and the presence of MSDs.